Analisis Modal Kerja dalam Pengendalian Likuiditas dan Profitabilitas Studi Kasus pada PT. Indocement Tunggal Prakarsa, Tbk. - Muktiadji, Nusa; Hidayat, Lukman; Melinda, Melinda (Jurnal Ilmiah Ranggagading (JIR), 2007)
Target of research is to know relation analysis and influence of working capital to likuiditas also company profitability, analysis done to know do amount of working capital have relation which are positive and influence which is signifikan to profitability and likuiditas. Result of research with method of SPSS indicate that a] 5 period that is year 2000 up to 2004, PT. Indocement Tunggal Prakarsa, Tbk have been able to manage working capital good enoughly. This matter is proved with working capital have relation which are positive to profitability is 0.6644 for gross proit margin and 0.927 for operation profit margin,and likuiditas is 0.9888 for current ratio and 0.9449 for quick ratio. Also working capital have influence which is signifikan to profitability is 0.4414 for gross profit margin and 0.86 for operation profit margin, and likuiditas is 0.9777 for current ratio and 0.8929 for quick ratio. Relation and influence relative always signifikan in per annum this, indicating that to go down to go up him mount company net working capital will influence indicator ratio of profitability and likuiditas. If working capital go up hence indicator ratio of likuiditas profitability and will experience of improvement, so also on the contrary. Therefore working capital better had by PT. Indocement Tunggal Prakarsa, Tbk have to fixed in number matching with requirement many company, so that storey level of likuiditas profitability storey level and can awake goodness. Keywords : Working Capital, Likuiditas, and Profitability.